Spontaneous Pneumomediastinum: A Possible Severe Condition in SARS-CoV-2 Pneumonia - Jacqmin, Geoffrey; Pirotte, Manuel; Caravaggio, Carlo; Devaux, Philippe (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Background Spontaneous pneumomediastinum (SP) is the presence of free air into extra-alveolar tissues within the mediastinum, without notion of trauma. This rare condition may occur as a complication of an underlying severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia. Higher rates of mechanical ventilation are reported in coronavirus disease 2019 (COVID-19) patients with pneumomediastinum.Case Description We report two cases of COVID-19 infected patients suffering from mild and severe SP and their outcome.Discussion The objective of this report is to review the literature about this condition. We discuss about the pathological pathways underlying this complication and how it reflects the severity of COVID-19 pneumonia.Conclusion Currently, it remains unclear if SP in SARS-CoV-2 pneumonia is a potential predictor of disease worsening, for it does not seem to be related with a higher rate of mortality.
Keywords: spontaneous pneumomediastinum; SARS-CoV-2; COVID-19